Hearing loss in children with growth hormone deficiency. (September 2017) - Muus, John S.; Weir, Forest W.; Kreicher, Kathryn L.; Bowlby, Deborah A.; Discolo, Christopher M.; Meyer, Ted A.
Abstract: Objective: Although insulin-like growth factor 1 (IGF-1) has been shown to be important for inner-ear development in animal models, little is known about the otologic and audiologic findings of children with growth hormone deficiency (GHD). The goal of this study is to evaluate the prevalence, type, and severity of hearing impairment in children with GHD. Methods: Audiologic, otologic, and demographic data were recorded for children with a diagnosis of GHD in the AudGen database. Data for each patient were selected based on the first encounter with available complete audiometric data or the first encounter with a type of hearing loss documented. The patients were then stratified by type and severity of hearing loss, and otologic issues were documented. A separate cohort comprised of children with GHD without hearing loss was compared as a control. Results: 209 children with GHD met inclusion criteria. 173 (83%) of these patients had hearing loss. 79% of losses were bilateral and 21% were unilateral (309 total ears with hearing loss). 293 of the 309 ears with hearing loss had audiograms with ear-specific thresholds; 47 had conductive, 24 had sensorineural, 65 had mixed and 157 had undefined hearing loss with incomplete audiograms. Pure-tone averages (PTA) were higher among patients with mixed hearing loss compared to patients with all other loss types. Conclusion: Hearing loss is prevalent in children with GHD with a predisposition to be bilateral. These findings suggest the need for increased awareness and routine hearing screening for patients with GHD. Further studies may elucidate the etiology of the hearing impairment in children with GHD to better aid pediatricians, endocrinologists, otolaryngologists and audiologists when assessing and managing these children.